External Borrowing and Inflation in Turkey from 2003-14; A Simple Linear Regression Analysis - Ekinci, Mehmet Behzat (International Journal of Economics and Financial Issues, 2016)
An economy using external resources can aim at several targets e.g. growth, public financing, covering a deficit in the balance of payments. However, external borrowing may result in some negative impacts such as a vicious cycle of increase in external debt, a decline in economic growth, huge budget deficits and an imbalance of payments in addition to inflation. This study examines the influence of external debts on inflation in Turkey from 2003-14. In this context, the effect of external debt is measured by means of a simple linear regression analysis using both the Consumer Price Index (CPI) and the Producer Price Index (PPI). The general opinion with regard to the effect of external debt on inflation is that they are positively related. Here this is confirmed for Turkey for the said period. The results show that both consumers and producers are negatively affected by external debt in terms of inflation. Keywords: External debt/borrowing; foreign debt/borrowing; inflation; CPI; PPI. JEL Classifications: E31; F34; H6